Improved staffing policies and practices in healthcare based on a conceptual model - Wei, Ning; Wang, Zhongwei; Li, Xiyuan; Zhang, Yibing; Zhang, Jing; Huang, Ziying; Wang, Xiao (Frontiers in Public Health, 2024)
Background Staffing policies are critical in healthcare facility. However, problems from mismatch between staff numbers requirements and offers are commonly encountered. This research tests the joint effects of quantitative and qualitative staff mismatch in a healthcare organization in China so to understand how staffing management policies condition staffing adequacy, and how staffing adequacy leads to important HR outcomes. Methods We have identified four dimensions of staffing management policies in a previous study, namely decision making, data management, productivity optimization, and title vs. competency. Based on this categorization, a 11-item scale was produced and its psychometric quality ascertained.A quantitative study was conducted with 1, 323 healthcare professionals (including clinical and administrative staff) working in the hospital, matched by dyads and teams. A conceptual model with work engagement as a mediator between quantitative staffing adequacy interactions with qualitative staffing adequacy in explaining team performance was tested with Structural Equations. Results Findings show staffing policies do exert effects on staffing adequacy. Findings also show quantitative and qualitative staffing adequacy interact in explaining work engagement and team performance and that the moderated mediation occurs as hypothesized. Conclusions Our findings suggest both types of staffing adequacies matter to promote higher team performance via a heightened sense of work engagement from healthcare professional. Furthermore, a modulation between the two types of staffing adequacies is observed during the promotion of higher team performance. The supported model is helpful to better design staffing management policies and increase the staffing fit so to improve hospital performance.